Capsaicin and carcinogenesis. Conflicting evidence regarding effects on carcinogenesis - Krzysztof Mariusz Halczuk; Bolesław Karwowski (Polish Pharmaceutical Society, 2024)
Study subject. Effect of capsaicin on tumorigenesis. Plants of the Capsicum family including chili peppers are one of the oldest domesticated crops. The constituents of chili peppers, particularly capsaicin, have become the subject of intense research because of their diverse effects on physiology and metabolism. The widespread use of capsaicin in various types of diseases has naturally led to attempts to use it to combat diseases that cause more than 25% of Poland's deaths - cancer. Purpose of the study. The purpose of the study was to gather and systematize knowledge on the effects of capsaicin and chili bell pepper extracts on tumorigenesis taking into account both its anticancer and prooncogenic properties described in the medical literature. Other properties of capsaicin resulting from its mechanism of action were also taken into account. Materials and Methods. The literature was reviewed by searching scientific databases: PubMed, ClinicalKey and Google Scholar. A search for relevant articles on chili peppers, capsaicin and their effects on tumorigenesis was conducted using the keywords "capsaicin" (Capsaicin), "cancer" (Cancer), TRPV1, "apoptosis" (Apoptosis), "oxidative stress" (Oxidative stress), "proliferation" (Proliferation), and in the following order: "obesity" (ang Obesity), "pain" (ang Pain). The present methodology made it possible to find current, both original and review papers on the properties of capsaicin, and in particular its effect on tumorigenesis. Results: Capsaicin, acts as an agonist of TRPV-1 receptors, which are widespread both in the nervous system (particularly in nopcyclic receptors) and outside nervous tissues. Studies indicate that the substance can effectively help regulate carbohydrate metabolism, help lower blood pressure, positively influence the lipid profile and reduce appetite. Thanks to these mechanisms, capsaicin can be used as an aid in the treatment of metabolic syndrome, obesity or type II diabetes. In the anti-cancer context, capsaicin shows the potential to inhibit cancer cell proliferation, induce apoptosis, reactivate the p53 protein and act as a radio- or chemosensitizer. Thanks to the discovery of its effects on the above mechanisms, capsaicin has been the subject of research for years into its use as an anticancer drug or an adjuvant to cancer treatment. Despite the promising results, there are conflicting reports on the effects of capsaicin on tumorigenesis. It seems that despite its undoubted anti-cancer effects confirmed by numerous studies, inappropriate use of capsaicin or products containing it may pose a risk of exacerbating existing cancer or the appearance of metastases. Conclusions: Despite its promising therapeutic properties, particularly in the anticancer context, the safety and efficacy of capsaicin remain controversial. Further research into the dose, duration of exposure and use of capsaicin is needed to accurately determine the scope of its applications and minimize possible negative side effects.